2015
DOI: 10.1371/journal.pone.0123811
|View full text |Cite
|
Sign up to set email alerts
|

MEVA - An Interactive Visualization Application for Validation of Multifaceted Meteorological Data with Multiple 3D Devices

Abstract: BackgroundTo achieve more realistic simulations, meteorologists develop and use models with increasing spatial and temporal resolution. The analyzing, comparing, and visualizing of resulting simulations becomes more and more challenging due to the growing amounts and multifaceted character of the data. Various data sources, numerous variables and multiple simulations lead to a complex database. Although a variety of software exists suited for the visualization of meteorological data, none of them fulfills all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Particle tracking, streamline rendering, and texture mapping are combined to build the hybrid flow environment. Dynamic texture mapping simulates Considering the multi-dimensional visualization models, Root Mean Square Error (RMSE) or r 2 are not suitable criteria, so Frame Per Second (FPS) and memory amount are used as the benchmark to evaluate the rendering efficiency quantitatively [39,40]. Table 2 shows the experimental results of the different rendering models and combinations.…”
Section: Performancementioning
confidence: 99%
“…Particle tracking, streamline rendering, and texture mapping are combined to build the hybrid flow environment. Dynamic texture mapping simulates Considering the multi-dimensional visualization models, Root Mean Square Error (RMSE) or r 2 are not suitable criteria, so Frame Per Second (FPS) and memory amount are used as the benchmark to evaluate the rendering efficiency quantitatively [39,40]. Table 2 shows the experimental results of the different rendering models and combinations.…”
Section: Performancementioning
confidence: 99%
“…In the framework of our project, the use of the Game Engine Unity enables us to combine the named methods (VA, 3D, VR) as well as to implement analysis methods and make them available via a graphical user interface (GUI) (Helbig et al, 2015). There is a need to develop effective and tailored tools for the visualisation and analysis of environmental data.…”
Section: Introductionmentioning
confidence: 99%
“…Other VR systems such as Multifaceted Environmental data Visualization Application (MEVA) have been applied to the analysis of geospatial data [83]. The MEVA system for geospatial visualization was usability tested in a CAVE environment and 88% of the participants suggested that they would use it for data analysis, 94% suggested they would use it for presentation and 81% would use it for exploration [83]. The positive experiences of participants using the MEVA system suggest that VR could also benefit an analysis of ecosystem services.…”
Section: Problem Statementmentioning
confidence: 99%
“…A visualization system, MEVA, was developed for simulating meteorological models [83]. MEVA and OpenGEOSys were applied to visualizing the Weather Research and Forecasting model (WRF) [82,83]. Both MEVA and OpenGEOSys utilized ParaView for data visualization.…”
Section: Geospatial Visualization Systemsmentioning
confidence: 99%
See 1 more Smart Citation